INNOVATIVE METHODS AND TOOLS IN HIGHER EDUCATION - Najmidinov Muzaffar; Yusupov Shahzodbek Bahadirovich; Kayumov Nodirbek Ghulam son; Yolchiyev Diorjon Davlatjon son (American Journals, 2022)
In the current era of information technologies, the use of innovative and electronic programs is finding its place not only in the IT field, but also in the education system. As a result of this, on the one hand, it will increase the computer literacy of students and professors, and on the other hand, it will allow us to organize the teaching and learning process remotely while preserving our health during the current COVID-19 pandemic. The purpose of the article is to improve the effectiveness of education through interactive methods and tools based on a number of changes in the higher education system, to make some recommendations for the development of distance education during the COVID-19 pandemic. In addition, the use of information and communication technologies for the innovative development of higher education, the use of educational platforms, and the use of higher education of Uzbekistan The experience of educational institutions is discussed.
Keywords: interactive communication, pedagogical software tools, communication service, pedagogical skills, creativity, innovative methods